SISTEM INFORMASI PENGELOLAAN ASET KENDARAAN BERMOTOR PADA STMIK RAHARJA TANGERANG - Diah Aryani; Muhamad Arif Nurdin; Pandi Baskara (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
The development of technology is currently growing rapidly and has been influential in the organization's activities to obtain data and information quickly. So the use of computers is essential in expediting and simplifying the process of data management to achieve the goal. In Higher Education Prog asset management reporting processes in motor vehicles is done manually resulting data search process and reporting of data assets requires significant time and too often there is missing data that affect the process of asset maintenance vehicles. It is therefore proposed to design a vehicle asset management information system using php and mysql. Which aims to be able to overcome the difficulty in finding the desired data and vehicle and asset maintenance delay in making the report.